A new species of Mimosa (Leguminosae, ser. Piresianae) from the Brazilian Midwest - Nogueira Hernandes P., Luan; Morales, Matias; Bagnatori Sartori, Angela Lucia B. (Magnolia Press, 2024)
A new species of Mimosa (Leguminosae, ser. Piresianae) from Brazil is described and illustrated in this article, along with a short description about the morphological and anatomical traits to fire-resilience in dry forests in Rupestrian Grasslands. In addition, we report the synopsis for the ser. Piresianae, its distribution, its habitat and provide an identification key for the species.